Restless legs syndrome and depression-anxiety disorder association in iron deficiency anemia patients - Yancar Demir, Esra; Özcan, Tuba; Özer, Feriha; Aşkan Parkaroğlu, Bilge; Enginyurt, Özgür; Çankaya, Soner (Ondokuz Mayis University, 2014)
Restless Legs Syndrome (RLS) is a disorder in which the person experiences a strong urge to move their legs or other extremities during rest. This urge to move is associated with tingling, pulling or other unpleasant and uncomfortable feelings; it usually slowly increases in the affected limb and often affects sleep. The incidence in general population is 5-15%. Although the pathophysiology is not fully understood, it was thought to result from the iron and dopamine metabolism irregularities and also has a genetic component. There are publications that show the frequency of disease in patients with iron deficiency or renal failure reaches up to 80%. In this study, we investigated the incidence of restless leg syndrome in anemic patients without any other organic disease or drug use, which can cause restless legs syndrome. We also tried to find out if there is a relation between restless legs syndrome, ferritin levels, anxiety and depression. Our retrospective, cross sectional study was made in The Ministry of Health and family medicine, neurology and psychiatry outpatient clinics of Ordu University Education and Research Hospital. 47 patients who were admitted to above mentioned clinics whose ferritin levels were under 50 ng/ml without any other disease and were not on medication (including those indicated for iron deficiency anemia) was included in to the study. All patients were given the Beck depression inventory and Beck anxiety inventory. The patients were questioned in terms of the basic diagnostic criteria established by International Restless Legs Syndrome Study Group. Definitive diagnosis could be established by the patients that meet the four criterias for the diagnosis. International Restless Legs Scale applied to patients diagnosed with RLS. Of 47 patients, 39 were female and 8 were male. 28 (%59.6) of the patients met the criteria of RLS. 28 patients with a diagnosis of RLS; 4 of them mild, 11 of them moderate, 8 of them severe and 5 of them experienced very severe symptoms of RLS. The relationship between the RLS and ferritin levels were checked and there was no statistically significant difference between them. A significant difference was not found in Beck depression scores between patients with and without RLS, but when the groups were compared in terms of Beck anxiety score, there were a significant difference. There was no significant relationship between RLS severity and Beck depression or Beck anxiety scores. RLS can be seen in %5-15 of general population and it is much more likely to emerge in the presence of an organic problem such as iron deficiency anemia. The diagnosis of the disorder is set clinically and RLS had a different significance because it may cause sleep disturbances and psychiatric disorders. If not questioned, this problem, which is not easily noticeable, can lead to misdiagnosis and misinterpreted as an anxiety disorder or a primary sleep disorder. Therefore the symptoms that could be corrected only by iron deficiency treatment, could be inşamed further by giving antidepressants and hypnotics.
Keywords: Anemia; Anxiety; Depression; Restless Legs Syndrome